1971
DOI: 10.1080/00071667108415898
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of the literature concerning the restricted feeding of growing pullets

Abstract: The sexual maturity of growing pullets can be retarded either by restricting calorie intake or by feeding a diet deficient in one or more essential amino acids, Several methods have been proposed for achieving either of these objectives. In this review the methods have been classified as (a) limiting the birds' time of access to food, (b) quantitative food restriction, (c) the use of low energy diets and (d) dietary protein restriction.Food restriction by limiting the time of access to food has given inconsist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0
2

Year Published

1974
1974
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 29 publications
7
38
0
2
Order By: Relevance
“…During this time, the chicks were affected by coccidiosis. Strain et al (1965) and Lee et al (1971) also observed that restricted birds were more prone to coccidiosis during their early period of life.…”
Section: Resultsmentioning
confidence: 98%
“…During this time, the chicks were affected by coccidiosis. Strain et al (1965) and Lee et al (1971) also observed that restricted birds were more prone to coccidiosis during their early period of life.…”
Section: Resultsmentioning
confidence: 98%
“…Lee et al (1971) also indicated that birds subjected to feed restriction made higher profit than the control. From the present study pigs fed 7.5%, and 5.5% of their body weight compared favourably tot hat fed the recommended 10% body weight.…”
Section: Feed Intake and Feed Conversion Ratiomentioning
confidence: 97%
“…Quantitative and qualitative feed Restriction for Monogastrics have been studied by Bows et al, (1988) who reported on the nature and levels of feed restriction that will not result in considerable weight loss and poor production. Food restriction and compensatory growth are an important phenomenon in temperate condition with food shortage in inter and re-alimentation in wt and dry seasons (Lee et al, 1971;Hogg, 1991). Conversely, in and semi-and areas food shortage occurs in dry season associated with thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Embora exista indicação de melhor desempenho de matrizes pesadas sujeitas à restrição de lisina durante o crescimento (COUCH et al, 1967), os resultados obtidos com poedeiras comerciais na fase de 0 a 6 semanas de idade têm contrariado esta observação, em virtude do aumento do canibalismo (LEE et al, 1971) e da queda permanente da produção e peso dos ovos (CONNOR et al, 1977).…”
Section: Introductionunclassified